In vitro evaluation of the antimicrobial activity of antiseptics against clinical Acinetobacter baumannii strains isolated from combat wounds - Denysko, Tetyana Valeriyivna; Nazarchuk, Oleksandr Adamovych; Gruzevskyi, Oleksandr; Bahniuk, Nataliia Ànatoliivna; Dmytriiev, Dmytro Valeriiovych; Chornopyschuk, Roman Mykolayovych; Bebyk, Vira Volodymyrivna (Frontiers in Microbiology, 2022)
Health care-associated infections (HCAIs) are among the most prominent medical problems around the world. In the context of increasing antibiotic resistance globally, the use of antiseptics as the main active agent and potentiator of antibiotics for the treatment of purulent-inflammatory complications of traumatic wounds, burns, surgical wounds can be considered to tackle opportunistic infections and their prevention during war. This study presents a comparative investigation of the antimicrobial efficacy of antiseptics used for surgical antisepsis and antiseptic treatment of skin, mucous membranes and wounds against multidrug-resistant clinical isolates of Acinetobacter baumannii as a wound pathogen of critical priority (according to the WHO). It was found that strains of A. baumannii, which have natural and acquired resistance to antimicrobial drugs, remain susceptible to modern antiseptics. Antiseptic drugs based on decamethoxine, chlorhexidine, octenidine, polyhexanide, povidone-iodine 10% and 2% provide effective bactericidal activity against A. baumannii within the working concentrations of these drugs. Chlorhexidine and decamethoxine are able to inhibit biofilm formation by A. baumannii cells. In terms of both bactericidal properties and inhibition of biofilm formation, chlorhexidine and decamethoxine are the most effective of all tested antiseptics.